Analysis of White Tofu Product Quality Control Using Statistical Process Control (SPC) at UD Novi Jaya in Sidoarjo Regency - Nur Fadila Sofiana; Rahmat Dhandy; Dini Nafisatul Mutmainah; Julia Agustina (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2026)
UD Novi Jaya is a tofu production business unit that has been operating for 20 years with a soybean processing capacity of 532 kg per day and produces 11,400 pieces of white tofu. However, the conventional production process causes variations in product losses. This study aims to identify the criteria and attributes of defects and analyze quality control by applying Statistical Process Control (SPC) analysis in white tofu quality control at UD Novi Jaya. This study is a quantitative descriptive study with a survey method. The analytical tools used are check sheets, control charts, Pareto diagrams, cause and effect diagrams, and process capabilities. The results of the p control chart analysis indicate two points outside the control limits on the soft tofu attribute, while statistical quality control is well controlled. The Pareto diagram shows that the main defect lies in the soft tofu attribute of 858 pieces. The cause and effect diagram on the soft tofu attribute shows the causal factors including materials, humans, methods, tools and machines, and the environment. Process capabilities show a high success rate on soft tofu, namely 96.2%. Suggested improvement efforts include sorting raw materials, training and supervision of workers, standardizing processes through standard operating procedures (SOPs), improving equipment and machinery, and improving cleanliness and environmentally friendly waste management.